Lincoln Cathedral
Some idea of dimensions of the dimensions of the reconstruction can be obtained from this distant view: the towers are later additions. The central tower: rebuilt in 1255 collapsed in 1239 and was not again rebuilt until 1307-11. Building was also delayed when in 1216 the barons captured the city of Lincoln in their struggle against the king, and appropriated 11,900 marks from building funds.